ACTIVATION OF COGNITIVE ACTIVITY OF FUTURE TEACHERS BY MEANS OF INTERACTIVE LEARNING (Pedagogy of Higher and Secondary Education, 2009)
In the article the author describes the role of interactive learning for the intensification of cognitive activity of students, gives examples of using of interactive methods at the lessons of practical course of English.
Keywords: interactive learning; intesification of cognitive activity; interactive methods